2020
DOI: 10.1002/bdd.2221
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of high‐dose methotrexate in Chinese pediatric patients with medulloblastoma

Abstract: Methotrexate (MTX) pharmacokinetics has substantial inter-individual variability and toxicity. In children with medulloblastoma treated with high-dose methotrexate (HD-MTX), the pharmacokinetic properties of methotrexate have not been established. A total of 660 serum samples from 105 pediatric patients with medulloblastoma were included in a population pharmacokinetic (PPK) analysis of methotrexate by using the nonlinear mixed-effects modeling method. The basic onecompartment population pharmacokinetic model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…Model-informed precision dosing is supported by the population approach, which leverages individual characteristics as parameters to predict more precisely the pharmacokinetic and pharmacodynamic outcomes and quantify the risk of severe adverse events. 5 Several HDMTX population pharmacokinetic models have been reported for paediatric patients, mainly with ALL or osteosarcoma, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] others were developed for adult patients, [21][22][23][24][25][26][27][28][29][30] and few have described HDMTX pharmacokinetics in children and adults simultaneously. 27,[31][32][33][34] To date, these models reflect the high inter-and intraindividual variability linked to chemotherapeutic protocols and patient physiological and pathophysiological characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Model-informed precision dosing is supported by the population approach, which leverages individual characteristics as parameters to predict more precisely the pharmacokinetic and pharmacodynamic outcomes and quantify the risk of severe adverse events. 5 Several HDMTX population pharmacokinetic models have been reported for paediatric patients, mainly with ALL or osteosarcoma, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] others were developed for adult patients, [21][22][23][24][25][26][27][28][29][30] and few have described HDMTX pharmacokinetics in children and adults simultaneously. 27,[31][32][33][34] To date, these models reflect the high inter-and intraindividual variability linked to chemotherapeutic protocols and patient physiological and pathophysiological characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The antileukemic effect of MTX is attributed to its competitive inhibition of dihydrofolate reductase (Galivan, 1980;Schmiegelow, 2009). HD-MTX is defined as a dose higher than 500 mg/m 2 , which could elicit a broad range of antitumor activities (Evans et al, 1986;Howard et al, 2016;Kawakatsu et al, 2019;Shi et al, 2020). It has been reported that HD-MTX can reduce the relapse rate, increase the event-free survival rate, and suppress the development of central nervous system (CNS) leukemia in childhood ALL (Balis et al, 1985;Evans et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, six studies included ALL patients greater than 13 years or infants and were excluded for further analysis [ 18 , 31 , 32 , 33 , 34 , 35 , 37 ]. In addition, one PopPK study was conducted on pediatric patients with osteosarcoma and was also excluded [ 38 ]. Finally, six PopPK models of MTX in ALL children were included for the external evaluation [ 11 , 19 , 20 , 21 , 26 , 36 ].…”
Section: Resultsmentioning
confidence: 99%